2020
DOI: 10.1166/jctn.2020.9139
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of High Cortisol Level in Increasing Incidence of Infection Cases Among Acute Stroke Patients

Abstract: Infection in the stroke was a treatment major problem, because it determines the prognosis. In the acute phase of stroke, high level cortisol may lead to a decreased immune system and patients tend to be more susceptible to infection. The correlation of serum cortisol level among acute stroke patients with incidence of infection was not fully investigated. The aim of this study was to determine the relationship between initial serum cortisol levels and the incidence of infection in acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Cortisol increases the availability of all fuel substrates such as increased glucose level and rapid mobilization of amino acids and fats from cells, making them available to various tissues and organs [ 6 ]. On the other hand, this response has been associated with ischemic neuronal injury [ 7 ], adverse cardiac effects including arrhythmias [ 8 ], and increased infections [ 9 ] contributing to increased mortality. Thus increase in cortisol levels has been linked to the severity or prognosis of AIS in various studies [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cortisol increases the availability of all fuel substrates such as increased glucose level and rapid mobilization of amino acids and fats from cells, making them available to various tissues and organs [ 6 ]. On the other hand, this response has been associated with ischemic neuronal injury [ 7 ], adverse cardiac effects including arrhythmias [ 8 ], and increased infections [ 9 ] contributing to increased mortality. Thus increase in cortisol levels has been linked to the severity or prognosis of AIS in various studies [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 Other problems are associated with the risk of infection in stroke patients. 3 Tumor necrosis factor alpha (TNF-α), together with other pro-inflammatory cytokines such as Interleukin-1b (IL-1b), IL-6 and IL-8, play a role in the ischemic injury of the central nervous system. Some experimental studies have shown that TNF-α has adverse effects on ischemic brain tissue.…”
Section: Introductionmentioning
confidence: 99%